Enhancing Community Knowledge and Skills in Organic Farming and Natural Dyes for Ikat Weaving in Ensaid Panjang, Sintang, West Kalimantan - Leksono, Amin Setyo; Mustafa, Irfan; Yanuwiadi, Bagyo; Turhadi, Turhadi; Afandhi, Aminudin; Zairina, Anisa (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
This community service program aimed to analyze the level of knowledge and identify strategies for introducing organic farming and natural dye production technologies for ikat weaving among the Dayak community in Ensaid Panjang Village, Sintang, West Kalimantan. The program employed an action research method with a problem-based learning approach. The activities began with a community needs assessment, followed by the delivery of materials and information through lectures, simulations, demonstrations, and training sessions. A total of 52 participants took part in the program. Among them, several informants were selected based on their knowledge and expertise. The key informants included the head of Ensaid Panjang Village, the Betang customary elders, and representatives from the Ensaid Panjang community. The results showed that three leading indicators demonstrated significant improvement in participants’ understanding. These included enhanced community skills in producing natural dyes from local plants for ikat weaving, the ability to process organic fertilizers from household waste, garbage, and animal manure, as well as the strengthening of institutional roles that support the production and marketing of woven fabrics. The substantial increase in understanding indicated that this program successfully improved participants’ knowledge and skills. Overall, the average increase in community understanding and achievement was 11%, with a notable 51% increase in knowledge of composting specifically.